Time in Afrofuturism, Classroom Time, and Carceral Time - Wendy W. Walters (Radical Teacher, 2022)
This essay describes teaching Afrofuturism in a small liberal arts college and a state prison, during the time of the pandemic. Questions about time are central to Afrofuturist literature, art, and scholarship, and the altered timeframes of both COVID and incarceration are placed into dialogue in this piece.